Anti-fouling foamed sole material with silk-like appearance, preparation method and application thereof
By using titanium dioxide modified synthesis of bismuth oxychloride fluorine mica powder and fluorine-containing silane coupling agent in sports sole materials, combined with EVA and other materials, the problem of easy dust and dirty stains in sports soles is solved, and the problem of sports soles is achieved. The combination of silk texture and high anti-fouling performance meets consumers' needs for special appearance and high anti-fouling performance.
Patent Information
- Application Number
- CN202310534913.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-05-12
AI Technical Summary
The existing sports sole material is easily contaminated with dust and dirty stains, causing the appearance to become old and difficult to meet consumers' needs for special appearance and high stain resistance.
The synthetic bismuth oxychloride fluorine mica powder modified with titanium dioxide was used for surface treatment and fluorosilane coupling agent, combined with EVA, POE, OBC and other materials, foamed sole materials with silk texture and good anti-fouling properties were prepared.
It realizes a silk-like appearance and elegant and luxurious texture, and at the same time improves the anti-fouling ability of foamed soles, meets consumers' special needs for sports midsoles, reduces the adhesion of dust and dirty stains, and maintains it for a long time. silk textured appearance.
Smart Images

Figure BDA0004225769560000071 
Figure BDA0004225769560000081 
Figure BDA0004225769560000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of footwear products, and in particular relates to an anti-fouling foamed sole material with a silk-textured appearance, a preparation method and an application thereof. Background Art
[0002] When consumers are shopping for sports shoes, the appearance design of the shoes gives them the most intuitive first impression. Therefore, whether a shoe product can become a commercial hit is closely related to whether its appearance design can meet the aesthetic needs of consumers. For sports shoes with similar functions in the industry, their different appearance designs are also taken into consideration by consumers, so it is particularly important to manufacture footwear products with special appearance styles.
[0003] The sole component is an important component of footwear products, mainly playing the role of support and anti-skid. On the other hand, the existing sports shoe soles are mostly made of EVA foam soles, TPU "popcorn" soles, and TPEE / PEBAX midsoles. These foam soles have a unique porous loose structure and are generally directly exposed to the external environment. However, they are easily contaminated with dust, dirt, etc. during wearing, causing the soles to become dirty and old. After a few days of wearing, the white soles of the shoes will turn yellow and gray, and need to be cleaned frequently, making daily care difficult. Therefore, foam soles with unique appearance and good anti-fouling ability can meet consumers' higher product demands. Summary of the invention
[0004] In view of this, the present invention provides an anti-fouling foamed sole material with a silk-like appearance and a preparation method and application thereof. The foamed sole provided by the present invention has a silk-like glossy appearance and good anti-fouling performance, which is conducive to application in sports shoes.
[0005] The present invention provides an anti-fouling foamed sole material with a silk-like appearance, which comprises the following raw material components in parts by weight:
[0006] EVA 50-70 parts, POE 5-15 parts, OBC 5-15 parts, EPDM 4-6 parts, styrene polymer 5-10 parts, titanium dioxide modified synthetic bismuth oxychloride-containing fluorine mica powder 5-12 parts, fluorine-containing silane coupling agent 0.5-2.4 parts, wear-resistant agent 5-8 parts, peroxide cross-linking agent 0.5-0.7 parts, foaming agent 2.5-3.0 parts, zinc oxide 1.0-1.2 parts, zinc stearate 1.2-1.5 parts, stearic acid 1.1-1.5 parts;
[0007] The titanium dioxide modified synthetic bismuth oxychloride fluorine mica powder and the fluorine-containing silane coupling agent are first mixed and then used; the ratio of the fluorine-containing silane coupling agent to the titanium dioxide modified synthetic bismuth oxychloride fluorine mica powder is 10%-20%:100%.
[0008] In order to realize an anti-fouling sole foam material with a unique silk texture and appearance, the present invention develops and improves the foaming formula and the preparation process. The foamed sole product produced not only has a silk-like glossy appearance, giving the product an elegant, luxurious, delicate, smooth, smart and graceful texture, which brings the charm of the product to the extreme, but also improves the anti-fouling ability of the foamed sole by cleverly matching fluorine-containing materials. It is a first in the industry and has great market potential.
[0009] The embodiment of the present invention first selects synthetic bismuth oxychloride-containing fluorine mica powder modified by titanium dioxide coating, which is conducive to forming a silk texture appearance; secondly, a fluorine-containing silane coupling agent is used to surface treat the synthetic bismuth oxychloride-containing fluorine mica powder modified by titanium dioxide coating. In parts by weight, the raw material components for preparing the anti-fouling foaming sole material described in the embodiment of the present invention include: 5-12 parts of synthetic bismuth oxychloride-containing fluorine mica powder modified by titanium dioxide, and 0.5-2.4 parts of fluorine-containing silane coupling agent. Specifically, 5-12 parts of synthetic bismuth oxychloride-containing fluorine mica powder modified by titanium dioxide and 0.5-2.4 parts of fluorine-containing silane coupling agent are heated and blended in proportion to obtain surface-modified mica powder.
[0010] Among them, the titanium dioxide modified synthetic bismuth oxychloride-containing fluorine mica powder can be commercially available, and the modified titanium dioxide is mainly coated on the surface of the fluorine-containing mica powder particles; the color of the titanium dioxide-coated modified synthetic bismuth oxychloride-containing fluorine mica powder specifically includes silvery white, gold, red, blue, purple, etc., and the preferred variety is silvery white powder. In an embodiment of the present invention, the titanium dioxide mass content in the titanium dioxide modified synthetic bismuth oxychloride-containing fluorine mica powder is 10% to 20%, and the main components are fluorine-containing mica (80% to 85%), titanium dioxide and bismuth oxychloride; in addition to the preferred silvery white color, its particle size can be 5-25μm. In an embodiment of the present invention, the fluorine-containing silane coupling agent is one or more of perfluorooctyl triethoxysilane, trifluoropropane trimethoxysilane and heptadecafluorodecyl trimethoxysilane; preferably one of these fluorine-containing silanes, and further preferred varieties: perfluorooctyl triethoxysilane F8261, commercially available.
[0011] The addition ratio of the above titanium dioxide modified synthetic bismuth oxychloride-containing fluorine mica powder in the foaming formula is 5 to 12 parts, for example, 6 parts, 8 parts, 9 parts, and 10 parts; the ratio of fluorine-containing silane to titanium dioxide modified synthetic bismuth oxychloride-containing fluorine mica powder is 10% to 20%: 100%. In a preferred embodiment of the present invention, the titanium dioxide coated modified synthetic bismuth oxychloride-containing fluorine mica powder and the fluorine-containing silane coupling agent are weighed in a ratio of 100%: 10% to 20% to obtain composition A, and composition A is placed in a high-speed mixer for mixing for 20-30 minutes (such as the stirring speed is set to 1000 rpm, and the heating temperature of the mixer is preferably set to 50 to 70°C), and then a dry surface-modified mica powder (which can be called composition B) is obtained.
[0012] The embodiment of the present invention can better maintain the silk texture appearance through the adsorption and penetration of the fluorine-containing silane in the fluorine-containing mica powder and the effect of covalent bonds, and the fluorine-containing mica powder is evenly dispersed in the matrix material. Moreover, due to the low surface energy of the fluorine-containing material, it can effectively prevent the surface adhesion of dust / stains, thereby improving the anti-fouling ability of the foamed sole and giving the product self-decontamination performance.
[0013] The base material of the antifouling foaming sole material described in the embodiment of the present invention is mainly: EVA 50-70 parts, POE 5-15 parts, OBC 5-15 parts, EPDM 4-6 parts, styrene polymer 5-10 parts. Among them, EVA is the main material, which is the English abbreviation of ethylene-vinyl acetate copolymer, and has the characteristics of good strength and elasticity. Compared with polyethylene (PE), EVA introduces vinyl acetate (VA) monomer into the molecular chain, thereby reducing high crystallinity and improving flexibility. In the embodiment of the present invention, the mass content of VA in the EVA is 21% to 33%, further 21% to 25%, and the weight part can be 50-65 parts; the preferred variety: EVA UE659 (Taiwan Polymer Chemical Co., Ltd.).
[0014] POE is the English abbreviation of polyolefin elastomer, mainly including ethylene-octene random copolymer, etc. It has better flexibility and resilience. Commercially available brands of ethylene-octene random copolymer can be used, and the preferred varieties are: POELC170 (LG Chemical Company); the mass proportion can be 6-10 parts.
[0015] The full name of OBC is block olefin copolymer, which has an ethylene-octene alternating block structure and has better comprehensive performance than other olefin copolymers. Its commercially available products may include grades with a hardness of 60-70A, and the preferred variety is: Infuse9007 (Dow Chemical Company); the mass parts may be 8 parts, 10 parts, 12 parts, 15 parts, etc.
[0016] EPDM is the abbreviation of ethylene propylene diene monomer rubber, which is a terpolymer of ethylene, propylene and non-conjugated diene, expressed as ethylene-propylene-non-conjugated diene terpolymer, with an ethylene structure mass content of 50-55%, and good performance; the preferred variety is EPDM4570P (Dow). The embodiments of the present invention can specifically use 5 parts or 6 parts of EPDM, and the corresponding commercially available products can be used.
[0017] The embodiment of the present invention also uses 5-10 parts of styrene polymers, preferably, the styrene polymers are selected from styrene-ethylene-butylene-styrene copolymers with a styrene content of less than 30%; the preferred varieties are SEBSYH530 (Baling Petrochemical Company), with an S content of 20%. SEBS is the abbreviation of a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenating polybutadiene as the middle elastic block, and has excellent aging resistance and mechanical properties; the embodiment of the present invention preferably includes 8-9 parts of SEBS.
[0018] If a white or colored midsole is to be produced, a commonly used technical solution is to use titanium dioxide or ultramarine pigment, masterbatch, etc. in the formula. However, when these colorants are added to produce a shoe midsole, the appearance is very ordinary and the texture is not distinctive, which makes it difficult to attract consumers and cannot meet their high aesthetic demands.
[0019] Based on the insight into consumers' psychology, the present invention aims to prepare a sports shoe sole foam material with a silk-textured appearance to meet consumers' special needs for the appearance of sports shoe midsoles and stimulate consumers' desire to buy; and improving the anti-fouling ability of the foamed sole can meet consumers' higher product demands.
[0020] The present invention mainly realizes the anti-fouling sports shoe foam sole with silk texture appearance through the following two preparation technologies: firstly, a certain ratio of the aforementioned titanium dioxide-coated modified synthetic bismuth oxychloride-containing fluorine mica powder is selected to ensure a certain special appearance.
[0021] Secondly, before the titanium dioxide-coated modified synthetic bismuth oxychloride-containing fluorine mica powder is added to the above-mentioned EVA matrix formula, it is preferably first surface treated with a fluorine-containing silane coupling agent in the above-mentioned proportion range. Through research and development, it was found that when the addition amount of the titanium dioxide-coated modified synthetic bismuth oxychloride-containing fluorine mica powder is less than 5 parts, the silk texture formed is not obvious; when the addition ratio is greater than 12 parts, there are problems with the dispersibility and compatibility of the mica powder in the formula, which not only causes flow marks on the surface of the sole, but also affects the bonding strength of the sole, increasing the risk of debonding.
[0022] In addition, because the dispersibility of synthetic bismuth oxychloride-containing fluorine mica powder in matrixes such as EVA, POE, and OBC is poor, and the compatibility is insufficient, it is necessary to modify the surface of the synthetic bismuth oxychloride-containing fluorine mica powder. The present invention selects a fluorine-containing silane coupling agent having the same fluorine atoms as the synthetic bismuth oxychloride-containing fluorine mica powder. According to the principle of similar compatibility, the fluorine-containing silane coupling agent has a better modification effect on the synthetic bismuth oxychloride-containing fluorine mica powder. On the one hand, the fluorine group of the fluorine-containing silane is connected to the synthetic bismuth oxychloride-containing fluorine mica powder, and on the other hand, the silane group is connected to the matrix such as EVA, POE, and OBC. Moreover, the adsorption and penetration of the fluorine-containing silane in the modified mica powder improves the overall anti-fouling ability of the foaming sole, and the silk texture appearance can be maintained more permanently.
[0023] In addition, the EVA matrix formula described in the embodiment of the present invention also adds 5-8 parts by mass of wear-resistant agent to ensure the performance. In the embodiment of the present invention, the wear-resistant agent is preferably a macromolecular silicone wear-resistant agent, such as MI of 1.0 g / min; the specific preferred commercial variety is wear-resistant agent A-108P (silicone granular wear-resistant agent, Xiamen Baishiyuan Industry and Trade Co., Ltd.).
[0024] The EVA component formula described in the embodiment of the present invention is mixed and foamed to form the antifouling foaming sole material; wherein the cross-linked foaming system is: 0.5-0.7 parts of peroxide crosslinking agent, 2.5-3.0 parts of foaming agent, 1.0-1.2 parts of zinc oxide, 1.2-1.5 parts of zinc stearate, and 1.1-1.5 parts of stearic acid. In an embodiment of the present invention, the peroxide crosslinking agent is one or two of diisopropylbenzene peroxide and 1,4-di-tert-butylperoxyisopropylbenzene, and BIBP is further preferred; diisopropylbenzene peroxide is also known as vulcanizing agent DCP, and 1,4-di-tert-butylperoxyisopropylbenzene is also known as BIBP. The foaming agent is preferably one or two of azodicarbonamide and N,N'-dinitrosopentamethylenetetramine, and more preferably foaming agent H (N,N'-dinitrosopentamethylenetetramine, Hangzhou Haihong Fine Chemical Co., Ltd.).
[0025] In the present invention, the addition of 1.0-1.2 parts of zinc oxide, 1.2-1.5 parts of zinc stearate and 1.1-1.5 parts of stearic acid can enhance crosslinking and processability, etc. Among them, the zinc oxide uses a grade with a zinc content greater than 99%, and the preferred variety is ZnO 997. More preferably, 1.0 parts of zinc oxide, 1.5 parts of stearic acid, and 1.5 parts of zinc stearate.
[0026] The embodiment of the present invention correspondingly provides a method for preparing the anti-fouling foamed sole material as described above, comprising: heating and blending 5-12 parts of synthetic bismuth oxychloride-containing fluorine mica powder modified with titanium dioxide and 0.5-2.4 parts of a fluorine-containing silane coupling agent to obtain surface-modified mica powder; mixing the surface-modified mica powder with 50-70 parts of EVA, 5-15 parts of POE, 5-15 parts of OBC, 4-6 parts of EPDM, 5-10 parts of styrene polymers, 5-8 parts of wear-resistant agents, 0.5-0.7 parts of peroxide cross-linking agents, 2.5-3.0 parts of foaming agents, 1.0-1.2 parts of zinc oxide, 1.2-1.5 parts of zinc stearate, and 1.1-1.5 parts of stearic acid, and obtaining the anti-fouling foamed sole material with a silk texture appearance through a foaming process.
[0027] Among them, the titanium dioxide modified synthetic bismuth oxychloride-containing fluorinated mica powder is surface treated to obtain the surface modified mica powder, and the process steps are as described above. After obtaining the dry surface modified mica powder, the embodiment of the present invention can prepare the foamed sole material through the MD process implementation steps. The content of each raw material is also as described above; the process flow specifically includes: weighing → mixing → granulation → small foaming → secondary compression molding. The implementation steps of the preferred embodiment of the present invention are described as follows:
[0028] Weighing materials: according to the dosage of the formula, weigh EVA, POE, OBC, EPDM, SEBS, wear-resistant agent and other materials as the first group; weigh composition B as the second group; weigh zinc stearate, zinc oxide, stearic acid as the third group; weigh the cross-linking agent and foaming agent as the fourth group.
[0029] Mixing: First, pour the first group of materials into the internal mixer, turn on the machine, and stir for 5-10 minutes when the temperature rises to 80-85℃; pour in the second group of materials and stir for 5-10 minutes; when the temperature rises to 90-95℃, pour in the third group of materials and stir for 5-10 minutes; when the temperature rises to 100-110℃, pour in the fourth group of materials, stir and mix for 10 minutes, and then pour out the mixed materials.
[0030] Granulation: Pour the mixed material into the granulator, and adjust the temperature of the first, second, third and fourth zones to 80, 85, 90 and 95°C respectively. Adjust the screw speed to 40-50 rpm and the cutting speed to 20-25 rpm.
[0031] Small foaming: Pour the prepared pellets into a flat-plate small foaming mold to complete the first foaming. The foaming temperature can be 170-180°C and the foaming time is 480-540 seconds.
[0032] Molding: The semi-finished product with small foams is left to cool for 24 hours, and then pressed into a flat-plate molding die to complete the finished product molding; preferably, the hot pressing temperature is 170-180°C, the hot pressing time is 380-420 seconds; the cooling water temperature is 25°C, and the cooling time is 400-420 seconds.
[0033] The foamed sole of the present invention is light, soft, highly elastic and wear-resistant through the secondary molding process and formula design. In the embodiment of the present invention, the anti-fouling foamed sole material has a silk texture appearance and a density of 0.173g / cm 3 In addition, the embodiment of the present invention also provides the use of the antifouling foam sole material as described above in the manufacture of sports shoes. The foam sole prepared in the embodiment of the present invention can not only maintain the functions of light weight, softness, high elasticity and wear resistance, but also the silky glossy appearance gives the product an elegant, luxurious, delicate, smooth, smart and graceful texture, which brings the charm of the product to the extreme, greatly enhances the value of the sports shoes, and improves the market competitiveness of the product. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0035] In order to further illustrate and understand the content of the present invention, the preparation method of the present invention is described in detail below in conjunction with the examples, but they should not be understood as limiting the scope of protection of the present invention. In the following examples, the raw materials used are all commercially available and conventional equipment is used.
[0036] Examples 1-12
[0037] The titanium dioxide-coated modified synthetic bismuth oxychloride-containing fluorine mica powder and the fluorine-containing silane coupling agent are weighed in a certain ratio to obtain composition A, and composition A is placed in a high-speed mixer and mixed for 20-30 minutes (the stirring speed is set to 1000 rpm, and the heating temperature of the mixer is set to 70°C) to obtain a dry surface-modified mica powder (composition B).
[0038] Weighing materials: According to the dosage of the formula in the table below, weigh EVA, POE, OBC, EPDM, SEBS, wear-resistant agent and other materials as the first group; weigh composition B as the second group; weigh zinc stearate, zinc oxide, stearic acid as the third group; weigh the cross-linking agent and foaming agent as the fourth group.
[0039] Mixing: First, pour the first group of materials into the internal mixer, turn on the machine, and stir for 5-10 minutes when the temperature rises to 80-85℃; pour in the second group of materials and stir for 5-10 minutes; when the temperature rises to 90-95℃, pour in the third group of materials and stir for 5-10 minutes; when the temperature rises to 100-110℃, pour in the fourth group of materials, stir and mix for 10 minutes, then pour out the mixed materials.
[0040] Granulation: Pour the mixed material into the granulator, and adjust the temperature of the first, second, third and fourth zones to 80, 85, 90 and 95°C respectively. Adjust the screw speed to 40-50 rpm and the cutting speed to 20-25 rpm.
[0041] Small foaming: Pour the prepared pellets into a flat-plate small foaming mold to complete the first foaming. The foaming temperature is 170-180°C and the foaming time is 480-540 seconds.
[0042] Molding: After the semi-finished product with small foams is cooled for 24 hours, it is pressed into a flat-plate molding mold to complete the finished product molding; the hot pressing temperature is: 170-180°C, the hot pressing time is: 380-420 seconds; the cooling water temperature is 25°C, and the cooling time is: 400-420 seconds.
[0043] In the comparative example, the second group of materials is titanium dioxide, or modified synthetic bismuth oxychloride-containing fluorine mica powder, etc.; for example, the modified fluorine-containing mica powder and the silane coupling agent are added, which are also mixed first and then added, but the ratio between the two is different from that in the embodiment.
[0044] Table 1 Formula of comparative example of the present invention
[0045]
[0046]
[0047] Table 2 Formula of Examples 1-5 of the present invention
[0048]
[0049] Table 3 Formula of Examples 6-12 of the present invention
[0050] composition Example 6 Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 EVAUE659 60 60 60 60 60 60 50 POE LC170 10 10 10 10 10 10 15 Infuse 9007 10 10 10 10 10 10 15 EPDM 4570P 5 5 5 5 5 5 5 SEBS YH530 9 9 9 9 9 9 9 Wear-resistant agent A-108P 6 6 6 6 6 6 6 Modified fluorine-containing mica powder 10 11 12 5 10 10 10 Fluorinated silane F8261 2.0 2.2 2.4 0.5 1.0 1.5 2.0 BIBP 0.65 0.7 0.7 0.55 0.6 0.6 0.6 Foaming agent H 2.8 2.9 3.0 2.6 2.7 2.7 2.7 Zinc stearate 1.5 1.5 1.5 1.5 1.5 1.5 1.5 ZnO 997 1.0 1.0 1.0 1.0 1.0 1.0 1.0 Stearic acid 1801 1.5 1.5 1.5 1.5 1.5 1.5 1.5
[0051] Among them, the sources of formula raw materials are as follows:
[0052] Titanium dioxide coated modified fluorine-containing mica powder: silvery white, particle size 5-25μm, including 15% titanium dioxide, 80% fluorine-containing mica, and 5% bismuth oxychloride, from Qingfeng Company.
[0053] Fluorinated silane coupling agent F8261: molecular weight 510.36, density 1.3299 g / cm 3 , Degussa Corporation.
[0054] EVAUE659: hardness 84A, VA content 25%, MI = 2.0g / 10min, Taiwan Polymer Chemical Co., Ltd.
[0055] POE LC170: hardness 71A, MI = 1.0g / 10min, LG Chemical Company.
[0056] Infuse 9007: Hardness 64A, MI=0.5g / 10min, Dow.
[0057] EPDM4570: ethylene content 50%, molecular weight 210,000, Mooney viscosity 70 (ML 1+4 / 125℃), Dow Chemical.
[0058] SEBS YH530: hardness 60A, S content 20%, Baling Petrochemical Company.
[0059] Wear resistant agent A-108P: silicone granular wear resistant agent, MI=1.0g / 10min, Xiamen Baishiyuan Industry and Trade Co., Ltd.
[0060] ZnO 997: Baishi brand zinc oxide, relative density 4.42~4.45, Hangzhou Haihong Fine Chemical Co., Ltd.
[0061] BIBP: 1,4-bis-tert-butylperoxyisopropylbenzene, Akzo Nobel.
[0062] Foaming agent H: N,N'-Dinitrosopentamethylenetetramine, Hangzhou Haihong Fine Chemical Co., Ltd.
[0063] Stearic acid 1801: Dukuda, Indonesia.
[0064] Zinc stearate: Huzhou Linghu Xinwang Chemical Co., Ltd.
[0065] Titanium dioxide R103: rutile titanium dioxide pigment, specific gravity 4.1, average particle size 0.23um, DuPont.
[0066] The performance tests of the shoe sole samples of the above embodiments and comparative examples were carried out, and the results are as follows:
[0067] Table 4 Comparison of mechanical properties data of comparative examples 1-6
[0068]
[0069] Table 5 Comparison of mechanical properties data of comparative examples 7-11
[0070] Serial number Test items Test methods Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 1 <![CDATA[Density g / cm 3 > DIN 53479 0.170 0.170 0.171 0.170 0.171 2 Hardness C DIN 55305 48 48 48 48 48 3 Rebound % DIN 53512 55 58 59 60 60 4 National standard wear marks GB / T 3093.2-2008 13.5 12.1 12.0 11.5 11.4 5 Compression deformation% ASTM-D.395-B 47 44 43 41 41 6 Delamination tearing N / CM DIN 53507-B 13 20 21 25 25 7 Tensile strength MPa DIN 53543 1.4 2.0 2.1 2.6 2.6 8 Adhesion strength GB / T 21396-2008 32 32 31 21 18 9 Glossiness EN1621-1:2012 22.4 21.7 21.8 22.1 22.2 10 Antifouling performance GB / T 30159.1-2013 2 2 2.5 3.5 3.5
[0071] Table 6 Comparison of mechanical properties data of Examples 1-6
[0072]
[0073]
[0074] Table 7 Comparison of mechanical properties data of Examples 7-12
[0075]
[0076] From the test results of Comparative Example 1 and Examples 1-12, it can be seen that the foamed material prepared by adding titanium dioxide has extremely low gloss and poor anti-fouling ability, while the foamed material added with modified synthetic bismuth oxychloride-containing fluorine mica powder and fluorine-containing silane coupling agent has gradually improved gloss and anti-fouling ability as the amount of the two added increases.
[0077] From the test results of Examples 1-9, it can be seen that as the amount of modified synthetic bismuth oxychloride-containing fluorine mica powder and fluorine-containing silane coupling agent added increases, the glossiness of the silk texture increases and the antifouling ability becomes stronger. Although the mechanical properties such as rebound, wear resistance, compression deformation, delamination tearing, and tensile strength decrease with the increase of the content of modified synthetic bismuth oxychloride-containing fluorine mica powder and fluorine-containing silane coupling agent, the decrease is relatively slight and still meets the mechanical property requirements of the midsole of sports shoes.
[0078] From the test results of Examples 1, 9 and Examples 6, 10, and 11, it can be seen that when the same amount of modified synthetic bismuth oxychloride fluorine mica powder is added, the proportion of the fluorine-containing silane coupling agent is adjusted to 10-20% (the proportion is calculated by the fluorine-containing silane coupling agent: the modified synthetic bismuth oxychloride fluorine mica powder), the changes in various properties are not much different, but the antifouling ability will increase with the increase of the fluorine-containing silane coupling agent. The test comparison of Example 6 and Comparative Examples 8-11 shows that when the proportion of the fluorine-containing silane coupling agent is 0-8%, the surface treatment effect of the modified synthetic bismuth oxychloride fluorine mica powder is poor, and the various mechanical properties and antifouling ability are significantly reduced. In particular, the test results of Comparative Examples 6 and 7 without the addition of the fluorine-containing silane coupling agent show that the modified synthetic bismuth oxychloride fluorine mica powder has not been surface treated and coupled with the fluorine-containing silane coupling agent, and its compression deformation, delamination tearing and tensile strength have dropped to the point where it does not meet the mechanical performance requirements of sports shoes. From the test results of Comparative Examples 10 and 11, it can be seen that when the proportion of the fluorinated silane coupling agent is further increased to 22-25%, its mechanical properties, glossiness, and antifouling properties are basically similar to those of the foaming material with a fluorinated silane coupling agent added at 20%, but with the addition of the fluorinated silane coupling agent, the bonding strength of the foaming material decreases, indicating that excessive addition of the fluorinated silane coupling agent will affect the bonding strength of the sole and increase the risk of the sole debonding. From the above summary, the addition ratio of the fluorinated silane coupling agent is preferably 10-20%.
[0079] By comparing the glossiness, antifouling performance and bonding strength of Comparative Examples 2-5 with those of Examples 1-8, it is found that: when the addition amount of the modified synthetic bismuth oxychloride-containing fluorine mica powder is 2-4 parts, the glossiness of the silk texture is not significantly improved, and the antifouling performance is also weak; when the addition amount of the modified synthetic bismuth oxychloride-containing fluorine mica powder is 5-12 parts, the glossiness of the silk texture and the antifouling performance meet the expected requirements. However, when the addition amount of the modified synthetic bismuth oxychloride-containing fluorine mica powder is 13 parts, the mechanical properties decrease significantly, and the bonding strength is 18N / cm, and the risk of debonding is relatively high. From the above, the addition amount of the modified synthetic bismuth oxychloride-containing fluorine mica powder in the formula of the present invention is 5-12 parts.
[0080] Remark:
[0081] Antifouling performance: GB / T 30159.1-2013 "Testing and evaluating the antifouling performance of textiles Part 1: Antifouling". Fix the sample in a test tube filled with specified solid dirt, place the sample flat on the sample fixing sheet, the fixing sheet is wrapped in the tube body, and a mixture of dust and high-pigment carbon black (dust: high-pigment carbon black = 75:25) is placed at the bottom of the tube as dirt. Turn the test tube over to make the sample fully contact with the dirt, roll 200 times, take out the sample, and use a hair dryer to blow away the dirt on the sample for rating. Use a gray card to compare the color difference between the stained and unstained parts of the test to evaluate the degree of staining resistance of the sample to solid dirt. When the color difference level of the test result is 3-4 or above, the sample is considered to be resistant to staining by solid dirt.
[0082] Compared with the existing sports shoe midsoles made of titanium dioxide, color powder and the like, the silk-like appearance of the present invention gives the sports shoe midsoles an elegant, luxurious, delicate, smooth, flexible and graceful texture, bringing the charm of sports shoes to the extreme and meeting the high aesthetic needs of consumers. In addition, the foamed soles prepared by the technology of the present invention have good anti-fouling ability, reduce the adhesion of dust / dirt during the wearing of sports shoes, and can maintain the silk texture appearance for a long time, so it has a high product value and market competitiveness.
[0083] The present invention cleverly selects synthetic bismuth oxychloride-containing fluorine mica powder coated with titanium dioxide with a high silk texture, wherein the bismuth oxychloride crystals are translucent square or octagonal, and the luster and deep effect of the crystals form a uniform and fine appearance with a strong silk luster, which can improve the glossiness of the fluorine-containing mica powder, thereby improving the silk texture and glossiness of the entire foamed sole (compared with the traditional EVA foamed midsole such as Comparative Example 1, the glossiness of the present invention is improved).
[0084] In order to improve the dispersibility and compatibility of the synthetic bismuth oxychloride-containing fluorine mica powder in the matrix, the present invention uses a fluorine-containing silane coupling agent containing the same fluorine element to perform surface modification on the modified fluorine mica powder. The fluorine-containing silane coupling agent can not only increase the dispersibility and compatibility of the fluorine-containing mica powder in the matrix, but also improve the antifouling property of the foamed sole. Through experimental exploration of the different addition amounts of the modified synthetic bismuth oxychloride-containing fluorine mica powder and the addition ratio of the fluorine-containing silane coupling agent in the formula, a foamed midsole with a higher silk texture gloss and good antifouling performance is finally obtained, while maintaining the mechanical properties of the foamed midsole, and not affecting the bonding strength between the foamed sole and the rubber outsole. Compared with the existing sports shoe midsoles with functions such as light weight, softness, high elasticity, wear resistance, shock absorption, and fatigue resistance, the present invention specifically gives the product a higher added value, which is a first in the industry.
[0085] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A silk-textured antifouling foamed sole material, characterized in that: In parts by weight, the raw material components include: EVA 50-70 parts, POE 5-15 parts, OBC 5-15 parts, EPDM 4-6 parts, styrene polymer 5-10 parts, titanium dioxide modified synthetic bismuth oxychloride-containing fluorine mica powder 5-12 parts, fluorine-containing silane coupling agent 0.5-2.4 parts, wear-resistant agent 5-8 parts, peroxide cross-linking agent 0.5-0.7 parts, foaming agent 2.5-3.0 parts, zinc oxide 1.0-1.2 parts, zinc stearate 1.2-1.5 parts, stearic acid 1.1-1.5 parts; The titanium dioxide modified synthetic bismuth oxychloride fluorine mica powder and the fluorine-containing silane coupling agent are first mixed and then used; the ratio of the fluorine-containing silane coupling agent to the titanium dioxide modified synthetic bismuth oxychloride fluorine mica powder is 10%-20%:100%.
2. The antifouling foaming sole material according to claim 1, characterized in that: The mass content of VA in the EVA is 21% to 33%; the OBC has a hardness of 60-70A.
3. The antifouling foaming sole material according to claim 1, characterized in that: The styrenic polymer is selected from styrene-ethylene-butylene-styrene copolymers with a styrene content of less than 30%.
4. The antifouling foaming sole material according to claim 1, characterized in that: The mass content of titanium dioxide in the titanium dioxide-modified synthetic bismuth oxychloride-containing fluorine mica powder is 10% to 20%.
5. The antifouling foaming sole material according to claim 4, characterized in that: The color of the titanium dioxide modified synthetic bismuth oxychloride-containing fluorine mica powder is silvery white.
6. The antifouling foaming sole material according to claim 1, characterized in that: The fluorine-containing silane coupling agent is one or more of perfluorooctyltriethoxysilane, trifluoropropanetrimethoxysilane and heptadecafluorodecyltrimethoxysilane.
7. The antifouling foam sole material according to claim 1, characterized in that: The wear-resistant agent is selected from macromolecular silicone wear-resistant agents.
8. The antifouling foaming sole material according to claim 1, characterized in that: The peroxide cross-linking agent is one or both of dicumyl peroxide and 1,4-di-tert-butyl peroxycumene; the foaming agent is one or both of azodicarbonamide and N,N'-dinitrosopentamethylenetetramine.
9. The antifouling foaming sole material according to any one of claims 1 to 8, characterized in that: The density of the antifouling foaming sole material is 0.173 g / cm 3 the following.
10. The method for preparing the antifouling foamed sole material according to any one of claims 1 to 9, comprising: 5-12 parts of titanium dioxide-modified synthetic bismuth oxychloride-containing fluorine mica powder and 0.5-2.4 parts of a fluorine-containing silane coupling agent are heated and mixed in proportion to obtain a surface-modified mica powder; The surface modified mica powder is mixed with 50-70 parts of EVA, 5-15 parts of POE, 5-15 parts of OBC, 4-6 parts of EPDM, 5-10 parts of styrene polymer, 5-8 parts of wear-resistant agent, 0.5-0.7 parts of peroxide cross-linking agent, 2.5-3.0 parts of foaming agent, 1.0-1.2 parts of zinc oxide, 1.2-1.5 parts of zinc stearate and 1.1-1.5 parts of stearic acid, and the anti-fouling foamed sole material with silk texture appearance is obtained through a foaming process.
11. Use of the antifouling foamed sole material according to any one of claims 1 to 9 in making sports shoes.
